Yawn contagion promotes motor synchrony in wild lions, Panthera leo. (April 2021) - Casetta, Grazia; Nolfo, Andrea Paolo; Palagi, Elisabetta
Abstract : Yawning, a fixed action pattern, is widespread in almost all vertebrate taxa. Several hypotheses have been proposed to explain the functions of yawning. These hypotheses, not mutually exclusive, can be conventionally arranged according to both physiological (e.g. drowsiness hypothesis: yawning when switching between sleep and being awake; arousal hypothesis: yawning in contexts of high social tension) and social communicative domains (e.g. contagion hypothesis, activity synchronization hypothesis). Owing to their high social cohesion and synchronized group activity, wild lions are a good model to investigate both spontaneous yawning from the physiological domain and, possibly, contagious yawning, from the social communicative domain. We videorecorded two groups of lions in the Makalali Reserve (Limpopo region, South Africa) and analysed their yawning behaviour. Spontaneous yawning was particularly frequent when the lions were relaxed and, in agreement with the 24 h activity cycle typical of the species, was similarly distributed over the night and day. These findings support the drowsiness hypothesis predicting that yawning is linked to the transition between sleeping and waking (and vice versa). Lions did not show high levels of yawning during competition over clumped food such as carcasses; hence, the arousal hypothesis was not supported. We found that yawn contagion was present, supporting the contagion hypothesis and the activity synchronization hypothesis. Our findings suggest that the convergence of motor behaviour triggered by yawn contagion (to our knowledge never explored in any other species) could represent an important tool to shed light on the adaptive and immediate benefits that underlie the evolution of the yawn contagion phenomenon in human and nonhuman animals. Highlights: Lions yawn when they are relaxed and engage in social affiliation. The arousal state seems to inhibit yawning in wild lions. Wild lions are infected by others' yawns. Yawn contagion facilitates motor convergence thus favouring lion group synchrony.